Academic Achievement Using Blended Teaching (face to face – Online) and its relationship with Serving in Tennis Players Aged 15 Years Old - Salman, Alaa Khudair; Jabbar, Hasnaa Staar (Journal of Physical Education, 2021)
The research aimed at identifying the relationship between academic achievement using blended learning (online and face to face) and performing serving in players from Babel national center for gifted in volleyball aged U15. The researchers used the descriptive method on (7) players for the season 2020 – 2021. The data was collected and treated using proper statistical operations to conclude a significant correlation relationship between academic achievement results and serving performance accuracy. Finally, the researcher recommended the necessity of using blended teaching because it saves time in repeating instruction. Blended learning is also important for all age groups and in addition to that, the researcher recommended making similar researches in other sports.